Juvenile Localized Scleroderma: A Very Rare Case (Delta Medical College Journal, 2015)
Juvenile localized scleroderma (JLS) is a rare chronic inflammatory and fibrosing disorder. It can result in significant morbidity, disfigurement, and severe functional, aesthetic and psychological disabilities. Patients with JLS should be identified early, evaluated extensively, treated aggressively, and monitored carefully. Here the case of a 2 year old boy is reported who was admitted into the department of Paediatrics of Delta Medical College & Hospital, Dhaka, Bangladesh with painful swelling of all fingers of both hands for 6 months and blackish patches over the fingers for the last one and half months. Left little finger was the first finger affected and there was flexion contracture of both left little and index fingers. The boy was diagnosed as a case of juvenile localized scleroderma and was confirmed by skin biopsy. We treated the child with methotrexate and prednisolone. It is very essential to raise awareness about this disease among clinicians and also parents for early diagnosis and treatment.Delta Med Col J. Jul 2015; 3(2): 96-101